2009
DOI: 10.3899/jrheum.080554
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and Reproduction in Male Patients with Ankylosing Spondylitis Treated with Infliximab: Table 1.

Abstract: Limited data are available concerning the effects of infliximab on semen quality. Our cases provide some evidence or reassurance for male patients treated with the anti-tumor necrosis factor-alpha agent. Further prospective studies are necessary, however, to guide clinicians in decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 28 publications
1
32
0
1
Order By: Relevance
“…However, at high tissue concentration, adverse effects on spermatogenesis have also been seen 2. Currently, there are no solid data indicating an impairment of spermatogenesis by TNF antagonists in men 3. A study of three men with SpA treated with infliximab for 8–24 months showed asthenozoospermia (reduced sperm motility) and teratozoospermia (abnormally shaped sperms), but there was no comparison with male patients not treated with TNF inhibitors or with healthy volunteers 4.…”
Section: Introductionmentioning
confidence: 99%
“…However, at high tissue concentration, adverse effects on spermatogenesis have also been seen 2. Currently, there are no solid data indicating an impairment of spermatogenesis by TNF antagonists in men 3. A study of three men with SpA treated with infliximab for 8–24 months showed asthenozoospermia (reduced sperm motility) and teratozoospermia (abnormally shaped sperms), but there was no comparison with male patients not treated with TNF inhibitors or with healthy volunteers 4.…”
Section: Introductionmentioning
confidence: 99%
“…The action of the TNF inhibitors on male hormone levels or fertility in general is not known, but the literature suggests an effect, which requires more investigation 9 . TNF-a cytokine inhibitors are associated with vasculitis and a crescentic glomerulonephritis 10 , but not in the absence of ANCA.…”
Section: Rheumatologymentioning
confidence: 99%
“…Small studies of the effect of infliximab on semen quality in male patients with CD and ankylosing spondylitis have reported a nonsignificant impact of biological agents on semen quality [106,107,108]. Data on indirect exposure to infliximab via the male patient within 3 months of conception were available for 10 patients with CD and rheumatoid arthritis: 9 live births and 1 spontaneous miscarriage (prior to 10 weeks of gestation) were reported.…”
Section: Biological Agents For Fertility the Mother-to-be And Duringmentioning
confidence: 99%